Buff- tip (Phalera bucephala L.) – a potential pest in energy plantations and agroforestry. Literature review from selected Internet sources - Bochniarz, Alina (Polish Journal of Agronomy, 2023)
Phalera bucephala belongs to the moth of Notodontidae family. The food plant list of its larvae covers many tree and shrub species, including those used in energy crops and agroforestry. The aim of this study was to collect and organise the information available in selected online literature databases on the buff-tip, taking into account scientific articles published in the last decade. In addition to a description of the insect’s appearance, the review covers issues concerning its occurrence, development, feeding mode, behaviour and relationship with other organisms. The summary also assesses the usefulness of the web sources used to characterise the species in question.